Lipoma in the pronator quadratus: A case report - Tian, Heng (Medicine (Baltimore), 2020)
RATIONALE: Lipomas are common benign tumors, constituting 16% of soft tissue mesenchymal tumors. They usually occur under the skin or in the large muscles of the thigh, shoulder, or upper arm. There are few reported cases of lipomas located in the forearm and hand muscles, accounting for less than 1% of all lipomas. PATIENT CONCERNS: A 47-year old man presented with a history of swelling and accompanying pain in the left wrist for 2 years. DIAGNOSES: The patient was diagnosed with intramuscular lipoma in the pronator quadratus. INTERVENTIONS: The mass was resected completely with wide-awake technique. OUTCOMES: The patient was followed up for 2 years with no recurrence. The symptoms of swelling and pain resolved within 3 weeks post-surgery, and there was no clear abnormality in wrist and finger movement and sensation. A satisfactory outcome was achieved. LESSONS: Intramuscular lipoma in the pronator quadratus is a rare benign tumor which should be distinguished from malignant tumors. Especially for patients with carpal tunnel syndrome presenting with wrist swelling, ultrasound, computed tomography, or magnetic resonance imaging can be used to assess deep tissue masses.